VD_FINDINFO Plainte / 2020 / 37 vom 5. November 2020 - VD Tribunal cantonal (2020)
DÉLAI DE RECOURS, FICTION DE LA NOTIFICATION, DÉCISION D'IRRECEVABILITÉ | 18 al. 1 LP, 31 LP, 138 al. 3 let. a CPC (CH)